Residual inflammation is a major determinant of myocardial recovery and cardiovascular outcome in takotsubo patients. (25th November 2020) - Lachmet-Thebaud, L; Marchandot, B; Matsushita, K; Sato, C; Dagrenat, C; Greciano, S; De Poli, F; Leddet, P; Peillex, M; Hess, S; Carmona, A; Reydel, A; et al.
Abstract: Background: Recent insights have emphasized the importance of myocardial and systemic inflammation in Takotsubo Syndrome (TTS). Objective: In a large registry of unselected patients, we sought to evaluate whether residual high inflammatory response (RHIR) could impact cardiovascular outcome after TTS. Methods: Patients with TTS were retrospectively included between 2008 and 2018 in three general hospitals. 385 patients with TTS were split into three subgroups, according to tertiles of C-reactive protein (CRP) levels at discharge (CRP<5.2 mg/l, CRP range 5.2 to 19 mg/l, and CRP>19 mg/L). The primary endpoint was the impact of RHIR, defined as CRP>19 mg/L at discharge, on cardiac death or hospitalization for heart failure. Results: Follow-up was obtained in 382 patients (99%) after a median of 747 days. RHIR patients were more likely to have a history of cancer or a physical trigger. Left ventricular ejection fraction (LVEF) at admission and at discharge were comparable between groups. By contrast, RHIR was associated with lower LVEF at follow-up (61.7 vs. 60.7 vs. 57.9%; p=0.004) and increased cardiac late mortality (0% vs. 0% vs. 10%; p=0.001). By multivariate Cox regression analysis, RHIR was an independent predictor of cardiac death or hospitalization for heart failure (hazard ratio: 1.97; 95% confidence interval: 1.11 to 3.49; p=0.02). Conclusions: RHIR was associated with impaired LVEF recovery and was evidenced as an independent factor of cardiovascular events. All together these findings underline RHIR patients as a high-risk subgroup, to target in future clinical trials with specific therapies to attenuate RHIR. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): GERCA (Groupe pour l'Enseignement, la prévention et la Recherche Cardiovasculaire en Alsace)